Influence of bacteria on compressive strength and permeation properties of concrete made with cement baghouse filter dust. (1st March 2016) - Siddique, Rafat; Nanda, Vasu; Kunal,; Kadri, El-Hadj; Iqbal Khan, M.; Singh, Malkit; Rajor, Anita
Highlights: Paper presents properties of bacterial concrete containing CBFD. Calcite producing bacteria improved the strength properties. Porosity and permeability increased with CBFD but reduced with bacteria. SEM and XRD analysis indicated the formation of calcite in bacterial concrete. Abstract: The present study investigated the influence of cement baghouse filter dust (CBFD) in control and bacterial concrete, as partial replacement of ordinary Portland cement (0%, 10%, 20% and 30%) on compressive strength, water absorption, porosity, chloride permeability and sorptivity at 28 and 56 days of curing. Calcite producing bacterial strain AKKR5 was mixed in water during concrete mixing with the cell concentration of 10 5 cells/mL. X-ray diffraction analysis confirmed the calcite production by bacterial strain. Control and bacterial concrete with 0% CBFD achieved best results for compressive strength of 32.89 and 34.66 N/mm 2, respectively, but with increasing the percentage of CBPD the compressive strength was decreased. Water absorption was significantly reduced in bacterial concrete compared to control concrete. The chloride permeability of concrete specimens containing control and bacterial CBFD concrete showed "moderate" to "low" permeability except 30% CBFD concrete with increasing curing period from 28 to 56 days. SEM and XRD results exhibited formation of ettringite in pores, increased calcium silicate hydrate (CSH) and calcite production which densified the concrete structure, and thus, increased the compressive strength in bacterial concrete containing CBFD. It was also found that CBFD is not cementitious in nature and replacing it with cement will reduce cement content. At 28 days, concrete mixture containing 10% CBFD exhibited compressive strength equivalent to target strength of 28 N/mm 2 required for designed control mix.